The effect of a body shape index on physical fitness index is more pronounced in boys than in girls: Evidence from a cross-sectional survey based on Tibetan adolescents aged 13–18 years in high-altitude areas of China - Tao Shi; Ke Guan; Chong Liu; Tao Zhang (PLoS ONE, 2026)
Background China is an important high-altitude region in the world, mainly inhabited by the Tibetan population. This study was conducted to understand the association between a body shape index (ABSI) and physical fitness index (PFI) among Tibetan adolescents in high-altitude areas of China. This study provides a reference for the improvement of physical fitness and the formulation of public health policies among Tibetan adolescents in high-altitude areas of China. Methods Using a stratified whole-group sampling method, 3819 Tibetan adolescents were selected from the high-altitude region of Ganzi, Sichuan, China, and tested on 8 items, including height, weight, waist circumference, grip strength, standing long jump, seated forward bend, 50-meter run, and endurance run (1000m/800m). ABSI and PFI were calculated, and Kruskal-Wallis H was used to compare PFI between groups. Linear regression analysis was used to analyze the correlations that existed between ABSI and PFI. Results The ABSI of Chinese Tibetan adolescents aged 13–18 years was (0.09 ± 0.01). Among them, ABSI was (0.09 ± 0.01) for boys and (0.09 ± 0.01) for girls, with no significant difference in comparison ( t = 1.594, P > 0.05). PFI [M(P 25 ,P 75 )] for Tibetan adolescents aged 13−18 years was −0.37 (−2.31,1.48), among them, PFI for boys was – 0.24 (−2.41,1.63) and the girl’s PFI was −0.46(−2.20,1.35), with no significant difference in comparison ( Z value = −0.878, P > 0.05). Overall, the comparison of PFI between the different ABSI groups (A, B, C, and D) was statistically significant ( P < 0.01) in all age groups except for the 17-year-old age group where there was no significant difference ( P > 0.05). Conclusion The ABSI level of Tibetan adolescents in high-altitude areas in China is low and negatively correlated with PFI. Compared with girls, the effect of ABSI on PFI was more obvious in boys. It is suggested that in the future, Tibetan adolescents in high-altitude areas should control the occurrence of waist circumference and overweight obesity and increase physical exercise to promote the physical fitness level of Tibetan adolescents.